Dissemination: Education Teacher Based on Gatra Eka Dharma Catur - Marzuki Marzuki; Sri Utami; Suhardi Marli (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
The problem of learning in primary schools is still prevalent in Melawi Regency is the image of teaching teachers who are still not integrated and cultivate the values contained in Catur Gatra (Pancasila, Teacher Hymn, Teacher Competence and Professionalism). Basically, this gatra catur is a unity of noble devotion. To practice and practice it requires a change of mindset - the teacher changes the paradigm of traditional teaching patterns to the mindset and act of educating contemporaries called change "teaching to learning". The purpose of this dissemination is to ground and practice catur gatra eka dharma teachers in Melawi. The method used is lecture, question and answer and simulation. Participants of the principals' dissemination activities, elementary school teachers, MI as many as 427 people, consisting of 225 women and 2002 men. The result of the questionnaire of dissemination activities distributed by the Committee Chairman is (1) the participants are very enthusiastic about the elimination of Catur Gatra (proven overflow of participants/teachers who previously prepared only 300 seats turned out to increase to 427) (2) teachers feel new insights about Chatur Gatra Eka Dharma as a form of noble devotion; (3) Through the descriptions of Catur Gatra it is expected that teachers can develop character education in Primary School / Madrasah Ibtida'iyah.